2018
DOI: 10.1136/ejhpharm-2018-001553
|View full text |Cite
|
Sign up to set email alerts
|

Stability study of hydromorphone and bupivacaine mixture by HPLC-UV

Abstract: ObjectivesThe objective of this study was to evaluate the physical and chemical stability of hydromorphone hydrochloride and bupivacaine hydrochloride in concentrations of 15 mg.ml-1 and 10 mg.mL-1 in 0.9% sodium chloride injection. Test samples of hydromorphone/bupivacaine mixtures were stored at 37°C, body temperature encounterd during continuous intrathecal infusion, for 90 days. The solutions were packaged in 20 ml plastic syringes. Evaluations for physical and chemical stability were performed initially a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Through literature survey it is found that there are many published methods for the determination of Bupivacaine levels in bulk drug, human plasma, urine and in mixtures using UV [9], HPLC [10][11], HPLC-UV, LC-MS [12][13][14][15], UPLC [16][17]. However, these previously reported methods have certain drawbacks like low sensitivity, low recovery, long retention time.…”
Section: İd İdmentioning
confidence: 99%
“…Through literature survey it is found that there are many published methods for the determination of Bupivacaine levels in bulk drug, human plasma, urine and in mixtures using UV [9], HPLC [10][11], HPLC-UV, LC-MS [12][13][14][15], UPLC [16][17]. However, these previously reported methods have certain drawbacks like low sensitivity, low recovery, long retention time.…”
Section: İd İdmentioning
confidence: 99%
“…So‐called physiological solutions are commonly used as compatible solvents for the parenteral administration of certain drugs [1–3]. In the case of an isotonic saline solution, the typical concentration of sodium chloride (NaCl) is ∼150 mM.…”
Section: Introductionmentioning
confidence: 99%
“…certain drugs [1][2][3]. In the case of an isotonic saline solution, the typical concentration of sodium chloride (NaCl) is ∼150 mM.…”
Section: Introductionmentioning
confidence: 99%